Análise inter e intra-observador no diagnóstico anátomo-patológico de endometriose - Rodrigo Hurtado (2008)
BACKGROUND: The criteria for the diagnosis of endometriosis are currently flexible to the extent of no longer requiring histological confirmation of the presence of endometrial glands and/or stroma. Physicians are encouraged to individualize treatments based on clinical signs and symptoms, impact on the quality of life or by simple presence of visible lesions that match the ASRM, 1997 revised classification system. OBJECTIVE: To determine whether histological microscopic evaluation of endometriosis is a reliable method for the diagnosis of endometriosis. METHODS: 68 women with clinical history for endometriosis were submitted to laparoscopic biopsy of visually suggestive peritoneal and/or ovarian tissue. Each biopsy sample was evaluated by three different pathologists and then once again by each of them to determine the intraobserver and interobserver variability of the histological examination. The results were analyzed by the Kappa integrity test to reveal whether microscopic examination, which is an observer-dependent method, is accurate for the diagnosis of endometriosis. RESULTS: All 68 patients had strongly suggestive clinical symptoms and laparoscopic findings that met the descriptive criteria of the 1997 revised ASRM classification. 38 (55.88%) of the biopsy samples showed histological evidence of endometriosis. The calculated values of Kappa of 0.78 for the interobserver variability and 0.88 for the intraobserver variability clearly demonstrate that the histological exam for endometriosis holds high integrity. CONCLUSION: The histological confirmation of endometriosis in only 55.88% of the biopsies suggest that laparoscopic visualization of lesions alone is not sufficient for the diagnosis of endometriosis. The integrity and reliability of the histological exam proven by the calculated values of Kappa (all above 0.60) state that this diagnostic tool should be reconsidered as an essential step in the diagnosis for suspected endometriosis.